Hepato-Splenic-Renal Polycystosis. - Croci, Fabio; Barreto, Miriam (Cirugía del Uruguay, 1987)
Study of a case of hepato-splenic-renal polycystosis, a congenital condltion of very low occurrence, found in an old woman with a dense record of renal problems. She had a serious complication in one of her cysts ap• pearing like an accesory biliary tract affection that led to a laparotomy due to error in the diagnosis. Etiopa• thogenic, anatomo-pathological, clinical, diagnostic and therapeutlc considerations on this affection are provided.